Compare Heart Rate Recovery and Cardiopulmonary Endurance of Badminton and Squash Player - Sumaiyah Obaid, Maham Nasir, Ateeqa Younis, Mian Waleed Ahmad, Mian Awais Ahmad, Nandisha Khalid, Fatima-Tul-Zahra, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Cardiopulmonary endurance is the ability to pump blood rich with oxygen to working muscles and this oxygen during exercise works and enhance period of activity. Regular aerobic exercises and sports can enhance cardiovascular endurance. Previous work in the field of physical science reveals that physical activity manage to advance and sustain higher levels of physical as well as cardiovascular fitness. Objectives: The main objectives of study were to compare heart rate recovery in badminton and squash healthy young adult players and to compare cardiopulmonary endurance among badminton and squash players. Methodology: 20 players with the age of 20-40 years playing badminton and squash for more than a yearfrom Liaquat Bagh Sports Complex, Rawalpindi were selected for this study. Subjects performed two tests for cardiopulmonary fitness testing i.e. Rockport walk test and 3 minutes step test. Subjects then played their regular game for 10 minutes. Heart rate, blood pressure, SpO2 were measured before the start of game, immediately after play and 5 minutes after cessation of game and heart rate recovery was calculated. Independent T test and Chi square test were applied to analyze the data. Results: When comparing heart rate recovery, results showed that people who were playing regular badminton showed faster heart rate recovery as compared to those individuals who were playing squash regularly. According to results of cardiopulmonary fitness test badminton players showed better result than squash players. Conclusion: Playing regular badminton for fitness purposes showed better results in cardiovascular health and heart rate recovery than playing squash Keywords: Badminton, Body Mass Index, Blood Pressure, Cardiopulmonary, Endurance, Heart Rate, Heart Rate Recovery, RatePerceived Exertion.